2017
DOI: 10.3126/jaar.v3i3.16857
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Use of Contraception among Married Women of Reproductive Age in a Rural Area of Nepal

Abstract: Background: Universal access to family planning is a human right, central to gender equality and women’s empowerment, and a key factor in reducing poverty. Use of contraception can prevent pregnancies related complication, helps in improving the health of mother and children and improve quality of life.Objective: to find out the predictors of use of contraception among married women of reproductive age (15-49 years).Methods: A descriptive cross-sectional study was adopted to find out the predictors of use of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…The analysis showed that working men had higher odds of using modern contraception than nonworkers, which was similar to the findings of other studies in Myanmar and Nepal. 16,26 Regarding wealth index and contraceptive use, our finding was similar to findings in DHS surveys in 18 countries in Asia, Africa, and Latin America and the Caribbean. 2 There was variation of adherence to modern contraceptive use in different wealth quintiles according to the type of modern methods.…”
Section: Discussionsupporting
confidence: 86%
“…The analysis showed that working men had higher odds of using modern contraception than nonworkers, which was similar to the findings of other studies in Myanmar and Nepal. 16,26 Regarding wealth index and contraceptive use, our finding was similar to findings in DHS surveys in 18 countries in Asia, Africa, and Latin America and the Caribbean. 2 There was variation of adherence to modern contraceptive use in different wealth quintiles according to the type of modern methods.…”
Section: Discussionsupporting
confidence: 86%
“…Data from the latest survey report shows that more than a half (53%) of currently married women of reproductive age had used FP method, of whom43 percent and 10 percent had used modern and traditional method respectively in 2016 (Ministry of Health;New ERA;& ICF, 2017).Many women from developing countries use contraceptives to prevent unplanned and unwanted pregnancies. Data show that there has been a gradual increase in utilization of contraceptives from 10 to 50 percent between the 1960s and the 1990s (Korra, 2002).Regardless of the enormous benefits of family planning services, their utilization still remains low in developing countries resulting into high rates of unwanted pregnancies, unplanned deliveries, unsafe abortions and maternal mortalities (Chaudhary, Dangol, Rai, & Rai, 2016). The Nepal Demographic and Health Survey [NDHS] 2016 shows that after an impressive increase in national contraceptive prevalence rate (CPR) in use of modern methods from 26 percent in 1996 to 44 percent in 2006, there has been no increase over the past 10 years; CPR remaining stagnant at 43 percent from 2011 to 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the variables such as age, level of education of respondents and her husband, occupation of the respondent's husband, level of discussion on family planning with husband, number of child, desired number of child, preferred family planning methods and sources of information on family planning services were statistically significant in chi-square test at 95% confidence intervals. The study done in a rural area of Nepal showed education status of husband, desire of children, spousal communication on contraception, husband approval on contraception and prior use of contraception were associated with use of contraception [22]. Moreover, other studies also revealed that age, educational status, number of children and spousal communication on modern contraceptives were associated with utilization of modern family planning methods [23][24][25].…”
Section: Discussionmentioning
confidence: 95%